Parametric survival analysis of menarche onset timing among Nigerian girls (2018)
Background: This study was a response to the dearth of information on the timing of menarche in low-income countries, and the need to update knowledge on the condition. It thereby enables the provision of adequate support to young girls during menarche. The study determined the timing and range of onset of menarche and identified the factors influencing the timing. Methods: We used data on girls’ sexual and reproductive processes from a nationally representative population survey of girls aged 15e24 years in Nigeria. Descriptive statistics, and survival analysis techniques were used for data analysis at p ¼ 0$05. Finding: A quarter of the respondents (26%) had commenced menstruation by age 12. Almost all, (90%) had experienced menstruation by age 17. Girls aged 20e24 years reported later menarche (time ratio 1$066, 95% CI: 1$045-1$087) compared to those aged 15e19 years. An increase of respondents age by one year resulted in 0$8% delay in onset timing. Significant differences were also found in the zone of residence among the sampled population. Compared with girls from the South East, the timing of menstruation was generally delayed among the girls from South-South by 5%, North Central by 9%, South West by 10%, North East by 16% and 17% among girls from the North West. Interpretation: There was a wide range in menarcheal age in Nigerian girls with a peak at 13e14 years and the possibility of a secular trend in the timing of onset. Early family life education is recommended.